Early life-history processes and their implications for the invasion of the barnacle Balanus glandula. Issue 4 (21st April 2017) - Robinson, Tamara B.; Pope, Haley R.; Alexander, Mhairi E.
ABSTRACT: As invasions become increasingly prevalent, it is important to understand how spread may be moderated by environmental conditions. This study considered the effect of location and changing substratum temperature on the early life-history processes of the alien barnacle Balanus glandula and its native comparator, Chthamalus dentatus, along the South African coast. Using settlement plates of different colours, temperature was manipulated to assess settlement, mortality, recruitment and growth of the two species. These variables were tracked over 10 weeks using repeat photography. Unexpectedly, there was no evidence of an effect of temperature on early life-history processes of either species. Settlement by the two barnacles was spatially segregated, with B. glandula occurring only on the West Coast where it is the dominant intertidal barnacle, while C. dentatus settled only on the South Coast, which has only recently been invaded by the alien. Despite this, it was notable that the relative settlement of B. glandula on rock was higher than that of C. dentatus . However, the lack of mortality of the native resulted in comparable levels of recruitment among the species. Nonetheless, the propensity of B. glandula to settle sporadically, coupled with fast growth, suggests that the invader may still possess the ability to become dominant along the newly invaded South Coast. This study highlights that measurements of early life-history parameters may not adequately predict the future range and impacts of alien species unless interpreted within the broader context of the nature of the recipient region and species-specific traits of the invader.